Ketahanan Masyarakat Pesisir terhadap Dampak Perubahan Iklim: Studi Kasus Nelayan dan Pelaku Usaha di Kecamatan Paku Haji - Jeremy Putra Pratama; Rohmansyah Rohmansyah; Laurensius Puntodewo; Fathin Aulia Rahman (Journal of Management and Social Sciences, 2025)
This research investigates the resilience of coastal communities in Desa Sukamulya, Kecamatan Paku Haji, in responding to the impacts of climate change. Using a quantitative approach with a survey method, data were collected from 40 respondents, including fishermen and coastal business actors. Findings reveal significant challenges faced by these communities, such as extreme weather, shifting fishing seasons, and declining fish catches, which negatively affect their economic sustainability. While awareness of climate change exists, gaps remain between understanding and actual adaptation efforts due to limited resources and inadequate infrastructure. The high dependency on fishing as a primary income source increases vulnerability, compounded by low savings, limited job diversification, and weak participation in social and cooperative networks. This study recommends enhancing livelihood diversification, improving coastal infrastructure, strengthening community organizations, providing climate education, and rehabilitating coastal ecosystems like mangroves and coral reefs. These strategies aim to bolster the resilience of coastal communities, ensuring better adaptation to climate change and the sustainability of their livelihoods.